2009
DOI: 10.3181/0809-rm-281
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dermal Sensitizing Potential of Traditional Medical Extracts in Local Lymph Node Assays

Abstract: Traditional medical extracts are commonly used as complex mixtures, which may contain naturally occurring contact sensitizers. In this investigation, the mice local lymph node assay (LLNA) was performed to evaluate the dermal sensitization potential of Myrrh, Borneolum, Olibanum, Moschus and Cassia Bark, which are widely used in topical traditional medication. In the radioactive LLNA, the stimulation index (SI) values were calculated for each medical extract. Myrrh, Borneolum, Olibanum and Moschus induced dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The major physical alteration induced by these tumors was the significant enlargement of the tumor-draining LNs. These enlarged LNs play active roles in tumor-induced lymph flow(Rudin et al, 2005; Lv et al, 2009). Thus, these methods may be useful not only for the identification and mapping of LNs but also for the diagnosis of tumor-associated changes in the LNs themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The major physical alteration induced by these tumors was the significant enlargement of the tumor-draining LNs. These enlarged LNs play active roles in tumor-induced lymph flow(Rudin et al, 2005; Lv et al, 2009). Thus, these methods may be useful not only for the identification and mapping of LNs but also for the diagnosis of tumor-associated changes in the LNs themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, it needs to be noted that the Tipton studies only examined fibroblast and epithelial cell types, not total (or various subclasses of ) leukocytes. Furthermore, a very recent paper showed that, in fact, treatment (albeit dermally rather than as here, per os) with myrrh resulted in significant induction of a response in a local lymph node assay that used CBA mice (Lv et al, 2009). In those studies, the Investigators were able to clearly show that as a result of myrrh, B220 + to CD3 + cell ratios (reflecting B-/T-cell ratios) and percentages of I-A k+ cells also positive for CD69 (CD69 + ; indicative of activated antigen-presenting cells) were increased in treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Even the literature on safety assessment in animal models is quite scarce considering the predominance of botanical ingredients in cosmetics. [12][13][14] The exact chemical composition of German chamomile depends on several variables, including chemotypes and edaphic conditions. Both nonvolatile and volatile organic components (VOCs) can be found in cosmetic preparations, in the form of extracts or essential oils, respectively.…”
Section: Introductionmentioning
confidence: 99%